2013
DOI: 10.1002/humu.22484
|View full text |Cite
|
Sign up to set email alerts
|

ICO Amplicon NGS Data Analysis: A Web Tool for Variant Detection in Common High-Risk Hereditary Cancer Genes Analyzed by Amplicon GS Junior Next-Generation Sequencing

Abstract: Next-generation sequencing (NGS) has revolutionized genomic research and is set to have a major impact on genetic diagnostics thanks to the advent of benchtop sequencers and flexible kits for targeted libraries. Among the main hurdles in NGS are the difficulty of performing bioinformatic analysis of the huge volume of data generated and the high number of false positive calls that could be obtained, depending on the NGS technology and the analysis pipeline. Here, we present the development of a free and user-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…This approach will be effective in quickly assessing the spectrum of SNPs in important genes or genomic regions affecting HC. Similar observations were also reported in other studies related to SNP discoveries in variety of diseases (Cheng et al 2010 ; Elliott et al 2012 ; Junemann et al 2012 ; Lopez-Doriga et al 2014 ). Our approach not only identify SNPs in exons, but also SNPs located in introns and up- and downstream regions, which have been recognised more important as playing important roles in gene regulation and diseases (Jaillon et al 2008 ).…”
Section: Discussionsupporting
confidence: 89%
“…This approach will be effective in quickly assessing the spectrum of SNPs in important genes or genomic regions affecting HC. Similar observations were also reported in other studies related to SNP discoveries in variety of diseases (Cheng et al 2010 ; Elliott et al 2012 ; Junemann et al 2012 ; Lopez-Doriga et al 2014 ). Our approach not only identify SNPs in exons, but also SNPs located in introns and up- and downstream regions, which have been recognised more important as playing important roles in gene regulation and diseases (Jaillon et al 2008 ).…”
Section: Discussionsupporting
confidence: 89%
“…The first study used some web tools, including BWA-MEM, Cutadapt, VarScan, and a series of functions and filters that they programmed. These authors suggested thresholds for optimal accuracy and recommended a 38-fold coverage range to detect heterozygous alleles with a minimum 25% allele frequency for a sensitivity of 99.9% 7 . The second study used Amplicon variant analyser software.…”
Section: Introductionmentioning
confidence: 99%